2005
DOI: 10.1002/jsfa.2206
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the levels of catechins and caffeine in tea beverage: estimated daily intakes and antioxidant activity

Abstract: Increased public awareness of health benefits of green tea is generally based on the high polyphenol content of tea leaves and the resulting beverage. A number of factors, such as species, season, agronomic condition and age of the leaves, are known to affect the composition of commercial teas. In the present study the effects of factors associated with domestic preparation and analytical methods, such as brewing time, concentration, solvent and type of tea product, on levels of catechins and caffeine, antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…The green tea phenolic compounds of highest concentration are gallic acid (GA), (−)‐gallocatechin (GC), (+)‐catechin (C), (−)‐epicatechin (EC), (−)‐epigallocatechin (EGC), (−)‐epicatechin gallate (ECG), (−)‐epigallocatechin gallate (EGCG), p ‐coumaroylquinic acid (CA), and (−)‐gallocatechin‐3‐gallate (GCG) (Fig. 1), with EGCG being the most abundant by weight 3, 4. Green tea also contains condensed and hydrolyzable tannins 5.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The green tea phenolic compounds of highest concentration are gallic acid (GA), (−)‐gallocatechin (GC), (+)‐catechin (C), (−)‐epicatechin (EC), (−)‐epigallocatechin (EGC), (−)‐epicatechin gallate (ECG), (−)‐epigallocatechin gallate (EGCG), p ‐coumaroylquinic acid (CA), and (−)‐gallocatechin‐3‐gallate (GCG) (Fig. 1), with EGCG being the most abundant by weight 3, 4. Green tea also contains condensed and hydrolyzable tannins 5.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of green tea polyphenols into tea is both time‐ and temperature‐dependent 3, 4. Tea preparation is important, as hot water preparation causes tea to be better at scavenging oxidative radicals than cold water preparations 7, which is likely due to greater extraction of polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…C. asiatica herbal tea obtained from the market is prepared by simple drying and is usually mixed with black tea to achieve a more yellow infusion. However, tea is known to contain high caffeine concentration (up to 23.79 g kg −1 )9 and has been reported to bring about adverse effects on human health 10. To avoid the intake of caffeine from tea mixed with C. asiatica herbal tea, fermentation of only C. asiatica leaves may be an alternative method and the process is believed to enhance the quality of herbal tea in terms of colour, flavour and taste 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…2 The most abundant polyphenol constituents are gallic acid (GA), (2)-gallocatechin (GC), (1)-catechin (C), (2)-epicatechin (EC), (2)-epigallocatechin (EGC), (2)-epicatechin gallate (ECG), (2)-epigallocatechin gallate (EGCG), p-coumaroylquinic acid (CA), and (2)-gallocatechin-3-gallate (GCG) (Figure 98.1), with EGCG contributing the highest concentrations compared to other GTPs. 3,4 Green tea also contains both condensed and hydrolyzable tannins. 5 Epidemiological studies have shown that green tea consumption is correlated with a lower incidence of many types of cancer, 6,7 yet these correlations are not universal.…”
Section: Introductionmentioning
confidence: 99%